Development of A Tracer Study Information System In Senior High School with Devops Method Using Python Application and Django Framework - Dony Novaliendry; Nathasya Utami Hakim (Jurnal Teknologi Informasi dan Pendidikan, 2022)
Technological developments are increasingly rapid so that it is no longer something that is not known to the public. The use of computers has developed, especially as an alternative in the assessment of school accreditation administration, including in the management of alumni data known as Tracer study. Tracer Study is an approach that allows institutions or higher education to obtain information about deficiencies that may occur in the educational process and learning process. Data management for alumni of Senior High School 1 Bukittinggi is dominated using paper media and data management is still difficult. By utilizing web technology, information can be accessed without any limitations of space and time. This is intended to facilitate the management of the alumni data list, which was initially still carried out using very commonly used applications, such as Microsoft being the Tracer Study system for Senior High School 1 Bukittinggi which will help manage alumni data. This system is designed using the Python programming language with the Django framework that utilizes the MVT architecture and is combined with the DevOps method, resulting in a system that can be used by schools to manage alumni data. This system provides several services, namely alumni search, filling out questionnaires, verifying reports, and exporting reports.